Assessment of the nursing process formulation among second-year students at a state university - Mangano, María Alejandra; Mercado, Sara Leonor (Revista Chilena de Enfermería, 2024)
Introduction: The Nursing Process is a foundational tool for the practice of the nursing profession, requiring cognitive, technical, and communication skills for its adequate implementation. Consequently, teaching and learning the Nursing Process entail certain complexities. Objectives: To describe the performance of second-year nursing students within an institution located in the province of Buenos Aires, Argentina, in the execution of the Nursing Process. Methodology: Descriptive, cross-sectional documentary study, with a quantitative emphasis. A total of 160 works were analyzed based on variables that describe the assessment, the diagnoses, and the care plans designed within the Nursing Process. Data analysis was carried out using simple descriptive statistics. Results: The study revealed that students encounter greater challenges in the stage of formulating actual and potential diagnoses, with percentages of 63.75% and 56.25%, respectively. Furthermore, difficulties were observed in identifying risk factors (63.75%) and prioritizing needs (55.63%). Additionally, the care activities lacked a coherent sequence that was aligned with the needs presented in the clinical case (57.50%). Conclusions: The difficulties identified through this study need to be resolved. To this end, a pedagogical intervention is proposed, centered on active learning, collaborative work, and constructive feedback. The implementation of theoretical-practical workshops featuring clinical case studies and peer evaluation is recommended. Furthermore, this proposed intervention could potentially be extended to other populations.